Acceptance model of precast concrete components in building construction based on Technology Acceptance Model (TAM) and Technology, Organization, and Environment (TOE) framework. (January 2022) - Katebi, Ali; Homami, Peyman; Najmeddin, Mohammad
Abstract: According to the increasing development of prefabrication as a sustainable alternative approach to conventional construction methods, the use of Precast Concrete Components (PCC) has received more attention. This method provides advantages such as improved construction speed, labor productivity, and lower waste of resources. It has also been suggested as an immediate response to the social need of housing demand. However, in some countries, most concrete buildings are still built using traditional methods. Considering the importance of promoting the use of PCC in building construction, this study aims to develop a model based on the Technology Acceptance Model (TAM) and the Technology, Organization, and Environment (TOE) framework to quantitatively investigate the influencing factors on adopting PCC from both individual and organizational perspectives. The proposed model was analyzed with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed improving engineers' understanding of PCC's advantages, strengthening the competitive atmosphere between organizations besides government support for builders to use PCC, had the greatest role in adopting this approach. In addition, the indirect effects of perceived risks and costs on PCC adoption through engineers' understanding of the benefits of this method were significant. The moderation effect of civil engineers' experience was also investigated on the relationship between influencing factors and intention to adopt PCC. The findings of this study may help economic and educational policymakers to develop prefabrication using PCC. New insights have also been presented by the current study to conduct more quantitative and qualitative research in the prefabrication context. Highlights: This paper presents a model for using precast concrete components by developing a TAM-TOE model. Perceived usefulness, competitive pressure, and government support affect the intention to adopt prefabrication. Perceived usefulness can mediate the effect of TOE variables on the intention to adopt precast concrete components. Engineers' working experience strengthens the intention to adopt precast concrete components. Costs and perceived risks indirectly affect the intention to adopt precast concrete components.